Presentation on occasion of launch of Value Added Tax & Excise Tax - Ram, Christopher (Ram & McRae [Georgetown]GY, 2006)
Highlights the purpose of the handbook. Indicates that the handbook is about the law and procedure of Value-Added Tax and the Excise Tax passed by the National Assembly.